The cost‐effectiveness of brief intervention versus brief treatment of Screening, Brief Intervention and Referral to Treatment (SBIRT) in the United States. (February 2017) - Barbosa, Carolina; Cowell, Alexander; Dowd, William; Landwehr, Justin; Aldridge, Arnie; Bray, Jeremy; Del Boca, Frances K.; Babor, Thomas F.; Bray, Jeremy W.
Abstract: Aims: To conduct a cost‐effectiveness analysis (CEA) comparing the delivery of brief intervention (BI) with brief treatment (BT) within Screening, Brief Intervention and Referral to Treatment (SBIRT) programs. Design: Quasi‐experimental differences in observed baseline characteristics between BI and BT patients were adjusted using propensity score techniques. Incremental comparison of costs and health outcomes associated with BI and BT. Setting: Health‐care settings in four US states participating in Substance Abuse and Mental Health Services Administration SBIRT grant programs. Participants: Ninety patients who received BT and 878 who received BI. Measurements: Per‐patient cost of SBIRT, patient demographics and six measures of substance use: proportion using alcohol, proportion using alcohol to intoxication, days of alcohol use, days of alcohol use to intoxication, proportion using drugs and days using drugs. Findings: BI and BT were associated with better outcomes. The cost of SBIRT was significantly higher for BT patients (75.54 versus 16.32, 95% confidence interval, P < 0.01). BT would be cost‐effective if the decision‐maker had a willingness to pay of 8.90 for a 1 percentage point reduction in the probability of using any alcohol. For the other five outcomes, BT was less effective and more costly, and BI would be a better use of resources. Conclusions: It might be cost‐effective to offer brief treatment if the goal is to abstain from alcohol. However, the higher effectiveness of brief treatment for this outcome is associated with considerable uncertainty and, because both brief intervention and brief treatment improve all outcomes, brief treatment does not appear to be a good use of resources.